2008
DOI: 10.1021/jo8016082
|View full text |Cite
|
Sign up to set email alerts
|

Highly Chemoselective Reductive Amination of Carbonyl Compounds Promoted by InCl3/Et3SiH/MeOH System

Abstract: A new strategy has been developed for reductive amination of aldehydes and ketones with the InCl3/Et3SiH/MeOH system, which is a nontoxic system with highly chemoselective and nonwater sensitive properties. The methodology can be applied to a variety of cyclic, acyclic, aromatic, and aliphatic amines. Functionalities including ester, hydroxyl, carboxylic acid, and olefin are found to be stable under our conditions. The reaction shows a first-order kinetics profile with respect to both InCl3 and Et3SiH. Spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(58 citation statements)
references
References 50 publications
1
57
0
Order By: Relevance
“…In contrast, organosilanes are mild and environmentally benign reducing agents, and in recent years, several reagent systems containing silanes such as Et 3 SiH/InCl 3 , [6] [7] PhSiH 3 / Bu 2 SnCl 2 , [8] PhSiH 3 /MoO 2 Cl 2 , [9] polymethylhydrosiloxane (PMHS)/TiA C H T U N G T R E N N U N G (O-i-Pr) 4 , [10] and polymethylhydrosil-A C H T U N G T R E N N U N G oxane (PMHS)/trifluoroacetic acid (TFA) [11] have also been employed in reductive amination.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, organosilanes are mild and environmentally benign reducing agents, and in recent years, several reagent systems containing silanes such as Et 3 SiH/InCl 3 , [6] [7] PhSiH 3 / Bu 2 SnCl 2 , [8] PhSiH 3 /MoO 2 Cl 2 , [9] polymethylhydrosiloxane (PMHS)/TiA C H T U N G T R E N N U N G (O-i-Pr) 4 , [10] and polymethylhydrosil-A C H T U N G T R E N N U N G oxane (PMHS)/trifluoroacetic acid (TFA) [11] have also been employed in reductive amination.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that salicylaldehyde, o-chlorobenzaldehyde and 2-chlorobenzaldehyde had low yields (entries 9, 10, 12), those probably due to the intramolecular hydrogen bond, electron withdrawing and steric effects for the aromatic aldehydes during this reaction. Besides, aliphatic aldehydes, regardless of whether they were linear or R-branched, underwent the reductive amination rapidly and gave the products in excellent yields nearly without the formation of any side products (entries [13][14][15]. Table 3 shows the results obtained for reactions carried using benzaldehyde with different nitrobenzenes.…”
Section: Catalytic Performancementioning
confidence: 99%
“…Due to their importance, several methods have been developed for the preparation of amines, such as direct base-promoted N-alkylation and direct reductive amination [3,4]. However, it's still a challenge to control the monoalkylation of primary amines [5], the synthesis of a wide variety of substituted amines relies heavily on the reductive amination of the carbonyl compounds [6,7], but the method is usually carried out with hydride-based reagents such as NaBH 4 [8], pyridine-BH 3 [9], Zn-AcOH [10], Et 3 SiH-CF 3 CO 2 H [11], Bu 3 SnHDMF [12], InCl 3 -Et 3 SiH [13], and various modified borohydride derivatives [14]. These reagents have certain limitations such as the dependence of a stoichiometric amount of reductant, poor functional group tolerance, side reactions, overalkylation, toxic waste, thermal instability, handling risks, and rigorous reaction conditions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although hydrogenation and transfer hydrogenation of C=N bonds in the presence of catalytic amounts of metal precursors are the most developed ways, catalytic hydrosilylation is a desirable choice because of mild reaction conditions and straightforwardness [17][18][19]. Indeed, during the last decades several reductive amination protocols based on transition metals or metal free catalysts have been reported [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. A number of catalysts rely on precious metals such as rhodium, ruthenium, and iridium.…”
Section: Introductionmentioning
confidence: 99%